Problems and prospects of development of environmental audit in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
Due to the deterioration of the ecological situation in the world are increasing requirements for compliance with generally accepted international standards of environmental safety. A number of legal and government documents regulating the development of the environmental policies of enterprises. It should be recognized that the organization, management and environmental audit, in its further development in Kazakhstan in terms of market economy currently reside in the center of attention of representatives of science and practice. A special place is occupied by the work of M.S. Yerzhanova pose a theoretical platform for the practical application of environmental audit in various business entities.
Keywords: Environmental audit; environmental codeks; audit procedures; environmental auditors; environmental taxes.